2011
DOI: 10.1016/j.neubiorev.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Common and distinct networks underlying reward valence and processing stages: A meta-analysis of functional neuroimaging studies

Abstract: To better understand the reward circuitry in human brain, we conducted activation likelihood estimation (ALE) and parametric voxel-based meta-analyses (PVM) on 142 neuroimaging studies that examined brain activation in reward-related tasks in healthy adults. We observed several core brain areas that participated in reward-related decision making, including the nucleus accumbens (NAcc), caudate, putamen, thalamus, orbitofrontal cortex (OFC), bilateral anterior insula, anterior (ACC) and posterior (PCC) cingulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

84
743
11
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 849 publications
(845 citation statements)
references
References 86 publications
84
743
11
7
Order By: Relevance
“…Clearly, source localisation of the valence effect at 300 ms could thus not give a meaningful result. In contrast, localisation of the proposed FRN component to the ventral striatum, combined with the finding that it codes exclusively for +RPEs, converges with recent fMRI meta-analyses showing the striatum to be strongly +RPE biased (Bartra et al, 2013;Garrison et al, 2013;Liu, Hairston, Schrier, & Fan, 2011). In these meta-analyses, the areas of the striatum responding to +RPEs were also relatively large, increasing the plausibility of their producing a scalp detectable voltage, something which has previously been questioned (Cohen, Cavanagh, & Slagter, 2011).…”
Section: Discussionsupporting
confidence: 64%
“…Clearly, source localisation of the valence effect at 300 ms could thus not give a meaningful result. In contrast, localisation of the proposed FRN component to the ventral striatum, combined with the finding that it codes exclusively for +RPEs, converges with recent fMRI meta-analyses showing the striatum to be strongly +RPE biased (Bartra et al, 2013;Garrison et al, 2013;Liu, Hairston, Schrier, & Fan, 2011). In these meta-analyses, the areas of the striatum responding to +RPEs were also relatively large, increasing the plausibility of their producing a scalp detectable voltage, something which has previously been questioned (Cohen, Cavanagh, & Slagter, 2011).…”
Section: Discussionsupporting
confidence: 64%
“…19,20 The posterior cingulate cortex plays an important part in altering behaviour in response to an unexpected change. 25 Animal and human studies have shown the relevance of this cortex in representing subjective value, particularly in relation to rewards, 26 and in error signalling after the omission of an expected reward. 27 The posterior cingulate typically responds to prediction error in conjunction with the ventromedial prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…There were no reliable differences between the patient groups. Reward processing is based on a neuronal circuitry including regions of the mesolimbic dopamine system, consisting of dopamine-producing midbrain nuclei (particularly VTA) and their subcortical (eg, NAcc) and cortical (eg, OFC and MPFC) target regions (Diekhof et al, Reward processing in UD and BD R Redlich et al 2008; Liu et al, 2011). The VTA-NAcc pathway seems to play a crucial role in reward processing, and its manipulation via dopaminergic transmission can regulate depression-like behavior (Keller et al, 2013).…”
Section: Reward Processing In Ud and Bdmentioning
confidence: 99%
“…Given the heterogeneity of previous studies, with different paradigms focusing on different aspects of reward processing, it is difficult to gain a clear picture. In a meta-analysis, Liu et al (2011) showed that reward outcome often activated the NAcc and medial orbitofrontal cortex, whereas reward anticipation activated the anterior cingulate cortex (ACC), insula, and areas within the brainstem.…”
Section: Introductionmentioning
confidence: 99%